A Detailed study on the Impact of Viral marketing on the Consumer Decision Process - Ritu Mehta; Jayesh Paliwal; Puneet kaur saini (Mumbai Lala Lajpatrai Institute of Management Journal of research, 2023)
Earlier marketing strategies were centered in how to get things on the market where they were subsequently purchased by customers Organizations had to improve their market and customer positioning as the economy grew. Viral marketing a strategy which enables people to distribute a message to to others has grown into one communication has become more crucial for business to sell themselves in the world of internet as communication has become more crucial If large number of receivers forward a message to large number of people the growth of message grows quickly. Business must adapt changes to remain competitive. Viral marketing can be used to increase brand awareness, leverage peer Influence and evoke emotional Responses.
Keywords: Viral Marketing; Consumer Buying; Social Media